Political Participation in Alevi Diaspora in the UK - Bilecen, Tuncay (Border Crossing, 2016)
Within migration flows from Turkey to Eurpoe it can be postulated that the UK has proportionally received more politically motivated migrants than other European destinations. The political migration from Turkey to the UK is marked with the catastrophic events that uprooted people such as 1971 coup d’état, 1978 massacres of Alevis in Maras and 1980 military coup d’état and is known to have peaked with the civil war in the 1990s in the Eastern provinces of Turkey. Hence the majority of the migrants from Turkey in the UK are Kurdish Alevis from eastern provinces such as Maras, Sivas, Kayseri and Tunceli. This research was conducted between September 2014 and September 2015. 60 individuals from Turkish speaking communities were recruited and semi-structured in-depth interviews were conducted. Interviews were transcribed and then analysed using tools of thematic data analysis. The findings indicated stronger interest in politics and higher level of political participation by Kurdish and Alevi participants. Hence this paper offers a detailedanalysis of political interest and political participation of Kurdish/Alevi community living in London. Three key areas are: i) how they organize themselves under the umbrella of British Alevi Federation; ii) their relationship with civil society organisations and ethnic economy, iii) their activities in order to create public interest and opinion in relation to what is happening in Turkey.